Recent advances in Blue-Emitting Iridium(III) Complexes Featuring 2-(2,4-Difluorophenyl)pyridine as the Cyclometalating Ligand - Zulkarnaen, Nur Khaliesa; Ali, Noorshida Mohd (Universitas Gadjah Mada, 2025)
The significance of blue emitters in the realization of cutting-edge organic light-emitting diode (OLED) displays cannot be overstated, leading to considerable efforts aimed at synthesizing intense blue phosphorescent Ir(III) complexes that are stable for use as dopants. Nevertheless, the quest for highly effective blue phosphorescent Ir(III) complexes remains fraught with challenges. Bis(2-(4,6-difluorophenyl)pyridinato-C2,N)(picolinato)iridium(III) (FIrpic), which employs 2-(2,4-difluorophenyl)pyridine (F2ppy) as the cyclometalating ligand and picolinic acid as the ancillary ligand, serves as a benchmark for blue phosphorescent Ir(III) complexes because of its outstanding performance in OLED devices, yet it still exhibits several limitations. Consequently, the pursuit of more effective blue phosphorescent iridium complexes remains a priority. In recent years, advancements in the field have focused on blue phosphorescent Ir(III) complexes utilizing a variety of cyclometalated ligands in conjunction with bidentate ancillary ligands, leading to extensive investigation. This discussion will highlight and analyze the most recent progress in designing and preparing those complexes, particularly utilizing F2ppy alongside diverse bidentate ancillary ligands. Future studies are encouraged to focus on structural modification of the F2ppy cyclometalating ligand, particularly with the combination of suitable ancillary ligands, to improve further color purity of blue-emitting Ir(III) complexes and their photophysical performance.